Anterior Cerebral Artery Stroke: Role of Collateral Systems on Infarct Topography. Issue 9 (September 2021) - Thirugnanachandran, Tharani; Beare, Richard; Mitchell, Melissa; Wong, Chloe; Vuong, Jason; Singhal, Shaloo; Slater, Lee-Anne; Hilton, James; Sinnott, Mathew; Srikanth, Velandai; Ma, Henry; Phan, Thanh
Abstract : Background and Purpose: The circle of Willis (CoW) and leptomeningeal anastomoses play an important role in transforming infarct topography following middle cerebral artery occlusion. Their role in infarct topography following anterior cerebral artery occlusion is not well understood. The aim of this study was to evaluate the role of the CoW and leptomeningeal anastomoses in modifying regional variation in infarct topography following occlusion of the anterior cerebral artery and its branches. Methods: Perfusion and magnetic resonance imaging of patients with anterior cerebral artery stroke and evidence of vessel occlusion were segmented and manually registered to standard brain template for voxel-wise comparison. Next, a computer model of the cerebral arteries was formulated as network of nodes connected by cylindrical pipes. The experiments included occlusion of successive branches of the anterior cerebral artery while the configurations of the CoW were varied. Results: Forty-seven patients with a median age of 77.5 years (interquartile range, 68.0–84.5 years) were studied. The regions with the highest probabilities of infarction were the superior frontal gyrus (probability =0.26) and anterior cingulate gyrus (probability =0.24). The regions around the posterior cingulate gyrus (probability =0.08), paracentral lobule (probability =0.05), precuneus and superior parietal lobule (probability =0.03) had a low probability of infarction. Following occlusions distal to the anterior communicating artery, the computer model demonstrated an increase in flow (>30%) in neighboring cortical arteries with leptomeningeal anastomoses. Conclusions: Traditionally the CoW has been regarded as the primary collateral system. However, our computer model shows that the CoW is only helpful in redirecting flow following proximal vessel occlusions (pre-anterior communicating artery). More important are leptomeningeal anastomoses, which play an essential role in distal vessel occlusions, influencing motor outcome by modifying the posterolateral extent of infarct topography. Abstract : Supplemental Digital Content is available in the text.